Differential Sensitivity of Nitrogen-Fixing, Azolla Microphylla to Organochlorine and Organophosphate Insecticide - W Raja; P Rathaur; R Ashiq (Journal of Applied Sciences and Environmental Management)
The development of the intensive agriculture in our country between 1960 and 1990 totally over passed the aspect connected with the negative impact of the toxic chemical compounds on the air, water and soil. Using chemical products as nutrients, fertilizers and pesticides, we believe that we attack our safety and we must know the effects of pesticides from these compounds. Application of pesticides in the paddy fields has deleterious effects on non-target organisms including Azolla which are photosynthesizing and nitrogen fixing micro-organisms contributing significantly towards soil fertility and crop yield. Pesticide contamination in the paddy fields has manifested into a serious global environmental concern. Present study was aimed to study the comparative effect of two such pesticides, a well-known species of Azolla, Azolla Microphylla were selected for their stress responses to an Organochlorine insecticide - Endosulfan, and Organophosphate insecticide-Monocrotophos with reference to their growth, Free radicals, Antioxidant enzymes and metabolites. Azolla microphylla strains were adversely affected by the insecticide doses and inhibition was dose dependent. But the highest decrease was seen in case of organochlorine insecticides. Pesticide treatment with increasing doses accelerated the formation of reactive oxygen species progressively, whereby an enhanced Antioxidant enzymes and metabolites were noticed in A. microphylla. On the other hand, increased amount of proline in all the insecticide treated concentrations was indicative of stressed activities of the organisms. In this work the effect of the insecticides on Azolla microphylla resulted in growth inhibition, a decline of physiological and biochemical activities but the highest effect was shown in case of organochlorine insecticide which is commonly used in the rice fields.